Shopes and markets - Burns, Peggy (Hove Wayland, 1988)
The book "Shops and Markets" by Peggy Burns, published in 1995 as part of the "Stepping Through History" series. This 32-page book provides a historical overview of the development of shops and markets from ancient times to the present day. It features illustrations of artifacts and paintings, fact boxes, maps, and a timeline to explain the evolution of commerce and its impact on people's lives. The book is designed to offer insights into how shopping and trading practices have changed over time and their significance in societal development.